Urban resilience in the COVID-19 pandemic and lessons learned post-pandemic: Case: Metropolitan City of Central Peru - Arana Velarde, Freddy; Uribe Hinostroza, Marilú; Casas Vásquez, María Cristina (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The context of an unexpected and lethal pandemic caused by the presence of COVID-19 in the present millennium shows that humanity was not prepared for such an event. This article shows that cities as human habitat systems are precarious in terms of organization, urban planning, comfort and safety, accompanied by inefficient public and private entities in urban management. In this context, the article presents the case of the metropolitan city of Huancayo, whose urban planning conditions and resilience to the emergency situation was precarious and highly inefficient to respond to the emergency.